Finite element analysis of the impact of different traction anchorage locations on maxillary molar distalization with clear aligners and implant screws - Xiangyu Ma; Chunmiao Jiang; Jie Zhang; Hong Ding; Qianwen Zhang; Zhijie Yang; Tianwei Shang; Cunhui Fan (BMC Oral Health)
Abstract Objective This study aims to evaluate the impact of different implant screw insertion sites and traction point combinations of clear aligners on anchorage control during maxillary molar distalization using a three-dimensional finite element analysis. Methods A finite element model was developed with the second maxillary molar distalized by 2 mm, followed by the distalization of the first maxillary molar by 0.25 mm. The control group, which did not include implant screws, was compared to two experimental groups (A and B), defined by the implant screw insertion sites: between the second premolar and first molar (Group A), and between the first and second molars (Group B). Each traction group was further subdivided (A1, A2, B1, B2) based on the clear aligner traction point location, which was either at the canine or first premolar. Three different force levels (100 g, 150 g, and 200 g) were applied to each group. The primary outcomes assessed were the distalization rate of the maxillary first molar, the three-dimensional displacement of each tooth, and the equivalent stress in the periodontal ligament under various conditions. Results All conditions resulted in distal movement of the first molar and mesial displacement of the remaining teeth.The control group achieved a first molar distalization rate of 58.76%. Among the traction groups, Group B2 demonstrated the highest distalization rate (59.44%) at 200 g. When compared to the other traction groups, B2 exhibited the greatest distalization of the first molar, while minimizing labial displacement of the incisors. However, this configuration also resulted in increased labial displacement of the canine. Conclusion The results suggest that implant screws placed between the first and second molars, combined with traction points at the first premolar using clear aligners, offer superior molar distalization efficiency and improved control over incisor anchorage during maxillary molar distalization.